2021
DOI: 10.1002/yea.3655
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of the methylotrophic yeast Komagataella phaffii grown under low‐ and high‐methanol conditions

Abstract: In this study, we analysed the intracellular fatty acid profiles of Komagataella phaffii during methylotrophic growth. K. phaffii grown on methanol had significantly lower total fatty acid contents in the cells compared with glucose‐grown cells. C18 and C16 fatty acids were the predominant fatty acids in K. phaffii, although the contents of odd‐chain fatty acids such as C17 fatty acids were also relatively high. Moreover, the intracellular fatty acid composition of K. phaffii changed in response to not only ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Despite these attractive features, methylotrophic yeast species exhibit a serious growth defect in a high methanol environment, thus preventing the construction of a highly productive methanol‐based fermentation system (Ma et al, 2021; Wakayama et al, 2016). In our previous study, shown in Figure 2, O. methanolica showed excellent methylotrophic growth until 3% methanol was reached, and in over 5% methanol conditions, the strain exhibited a severe growth defect (Wakayama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these attractive features, methylotrophic yeast species exhibit a serious growth defect in a high methanol environment, thus preventing the construction of a highly productive methanol‐based fermentation system (Ma et al, 2021; Wakayama et al, 2016). In our previous study, shown in Figure 2, O. methanolica showed excellent methylotrophic growth until 3% methanol was reached, and in over 5% methanol conditions, the strain exhibited a severe growth defect (Wakayama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%